Use of diets with Moringa oleifera (stems + leaves) meals in laying hens - Valdivié, Manuel; Rodríguez, Bárbara (Cuban Journal of Agricultural Science, 2016)
An amount of 36 L-33 laying hens, with 1618 g of liveweight and more than 80 % of laying, were used in order to evaluate productive performance of diets with 0, 10 and 20 % of Moringa oleifera meal, from 34 to 50 weeks of age. Birds were kept in individual cages, at a rate of 12 hens/treatment, according to a completely randomized design, with three treatments and 12 repetitions. Performance of laying hens had no differences among treatments with 0 and 10 % of moringa for variability(100 %), liveweight (1756 to 1765 g/bird), food intake (110 g/bird) and egg production (76 to 81 %). However, with 20 % of moringa on the diet, there was a reduction of laying in 14 % regarding control treatment. Moringa favored pigmentation of egg yolks. With 10 % of moringa, cost of needed food to produce a thousand eggs was lower than control. From a nutritional point of view,it was evident the possibility of using up to 10 % of Moringa oleifera (stems + leaves) meal in diets for laying hens between 34 and 50 weeks of age.Key words: forage, moringa, laying hens